Simultaneous Identification of Clinically Common Vibrio parahaemolyticus Serotypes Using Probe Melting Curve Analysis - Li, Minxu; Jiang, Yixiang; Shi, Xiaolu; Li, Yinghui; Jiang, Min; Lin, Yiman; Qiu, Yaqun; Zuo, Le; Deng, Yinhua; Lin, Zeren; Liao, Yiqun; Li, Qingge; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
The dynamic nature of Vibrio parahaemolyticus epidemiology has presented a unique challenge for disease intervention strategies. Despite the continued rise of disease incidence and outbreaks of vibriosis, as well as the global emergence of pandemic clones and serovariants with enhanced virulence, there is a paucity of molecular methods for the serotyping of V. parahaemolyticus strains to improve disease surveillance and outbreak investigations. We describe the development of a multiplex ligation reaction based on probe melting curve analysis (MLMA) for the simultaneous identification of 11 clinically most common V. parahaemolyticus serotypes spanning a 10-year period. Through extensive sequence analyses using 446 genomes, specific primers and probes were designed for a total of 22 antigen gene targets for the O- and K- serogroups. Additionally, the toxR gene was incorporated into the assay for the confirmation of V. parahaemolyticus. All gene targets were detected by the assay and gave expected Tm values, without any cross reactions between the 11 clinically common serotypes or with 38 other serotypes. The limit of identification for all gene targets ranged from 0.1ng/uL to 1ng/uL. The intra- and inter-assay standard deviations and the coefficients of variation were no more than 1°C and less than 1% respectively, indicating a highly reproducible assay. A multicenter double-blind clinical study was conducted using the traditional V. parahaemolyticus identification workflow and the MLMA assay workflow in parallel. From consecutive diarrheal stool specimens (n=6118) collected over a year at 10 sentinel hospitals, a total of 153 V. parahaemolyticus isolates (2.5%) were identified by both workflows. A total agreement (kappa=1.0) between the serotypes identified by the MLMA assay and conventional serological method was demonstrated. This is the first molecular assay to simultaneously identify multiple clinically important V. parahaemolyticus serotypes, which satisfies the acute need for a practical, rapid and robust identification of V. parahaemolyticus serotypes to facilitate the timely detection of vibriosis outbreaks and surveillance.